Effect of Replacement of Tubifex sp. with Commercial Shrimp Pellets for Growth and Survival Rate of Climbing Perch (Anabas testudineus) - Jordi Edwin Gurning; Hamdan Alawi; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from October 29th 2015 until November 26th 2015 at Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau. The aim of this research was to determine subtitusion (Tubifex sp.) with commercial shrimp pellets for the growth and survival Rate of climbing perch (Anabas testudineus) larvae. The method used was an experimental method by using a completely randomized design (CRD) with five treatments and three replications. Treatments applied were T4PU0 (Tubifex sp. four week), T3PU1 (Tubifex sp. three week + commercial shrimp pellets one week), T2PU2 (Tubifex sp. two week + commercial shrimp pellets two week), T1PU3 (Tubifex sp. one week + commercial shrimp pellets three week). T0 PU4 (commercial shrimp pellets four week). The results showed that larvae fed on T3PU1 (Tubifex sp. three week + commercial shrimp pellets one week), average of absolute length 3,06 cm, average of absolute weight 0,745 g, and spesific growth rate 15,41%, with the highest survival rate on T2PU2 (Tubifex sp. two week + commercial shrimp pellets two week) 86,67%. Results of water quality measurements in the temperature, pH and dissolved oxygen was 27–290 C, 4,5-6,9 and 2,3 – 6,9 ppm/L respectively.Keyword: Climbing perch larvae (Anabas testudineus), growth, survival rate, commercial shrimp pellets